2016
DOI: 10.15252/embj.201694615
|View full text |Cite
|
Sign up to set email alerts
|

IL ‐1 signaling is critical for expansion but not generation of autoreactive GMCSF + Th17 cells

Abstract: Interleukin-1 (IL-1) is implicated in numerous pathologies, including multiple sclerosis and its animal model experimental autoimmune encephalomyelitis (EAE). However, the exact mechanism by which IL-1 is involved in the generation of pathogenic T cells and in disease development remains largely unknown. We found that following EAE induction, pertussis toxin administration leads to IL-1 receptor type 1 (IL-1R1)-dependent IL-1b expression by myeloid cells in the draining lymph nodes. This myeloid-derived IL-1b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
(109 reference statements)
2
46
0
Order By: Relevance
“…Schiffenbauer et al first reported that IL-1R-deficient mice (on a mixed genetic background) were resistant to active EAE induction (28). Their results have been confirmed by several other groups using IL-1R-deficient mice on the C57BL/6 background (2934), although the degree to which these mice were protected from clinical disease was somewhat variable. Despite one report to the contrary (35), IL-1β appears to be the critical mediator of EAE, rather than IL-1α, as IL-1β-deficient mice were seen to resist EAE by two groups (33, 36), while IL-1α-deficient mice remained susceptible (33, 35).…”
Section: Established Associations Between Il-1 and Autoimmune Neuroinsupporting
confidence: 53%
See 4 more Smart Citations
“…Schiffenbauer et al first reported that IL-1R-deficient mice (on a mixed genetic background) were resistant to active EAE induction (28). Their results have been confirmed by several other groups using IL-1R-deficient mice on the C57BL/6 background (2934), although the degree to which these mice were protected from clinical disease was somewhat variable. Despite one report to the contrary (35), IL-1β appears to be the critical mediator of EAE, rather than IL-1α, as IL-1β-deficient mice were seen to resist EAE by two groups (33, 36), while IL-1α-deficient mice remained susceptible (33, 35).…”
Section: Established Associations Between Il-1 and Autoimmune Neuroinsupporting
confidence: 53%
“…Because IL-1R1 knockout mice resisted active EAE induction but were susceptible to EAE when they served as recipients for adoptively transferred IL-1R-sufficient MOG-specific T H 17 cells, Sutton et al reasoned that T H 17 cells themselves must be critical responders to IL-1β (29). Furthermore, Rag1 -deficient mice reconstituted with IL-1R1-deficient CD4 + T cells (77) and mice with T cell-specific ablation of IL-1R1 ( Il1r1 fl/fl Cd4 -Cre) developed milder clinical EAE after immunization (34), confirming a T H cell-intrinsic role for IL-1 responsiveness. Ghoreschi et al demonstrated that IL-1β in combination with IL-6 and IL-23 was critically required for the generation of pathogenic T H 17 cells using a system of adoptively transferred in vitro polarized MOG-specific 2D2 TCR transgenic T H cells (78).…”
Section: Il-1β Acts On Th Cells To Promote Pathogenicity In Eaementioning
confidence: 96%
See 3 more Smart Citations